Step-by-step explanation:
the question is not correct
edit it and I will answer u in comments
Good morning,
Answer:
<h2>5+(-4) > -4 + (-7)</h2>
Step-by-step explanation:
5+(-4) = 5 - 4 = 1
-4 + (-7) = -(4+7) = -11
since 1 > -11 then 5+(-4) > -4 + (-7)
:)
Answer:
271 miles
Step-by-step explanation:
15.95+0.92 x=265.27
0.92 x=265.27-15.95
.92 x=249.32
x=24932/92=271
Answer:
lower price = 3
higher price =11
Step-by-step explanation:
p(x) = -2(x-3) (x-11)
Setting equal to zero
0 = -2(x-3) (x-11)
Using the zero product property
x-3 = 0 x-11 =0
x=3 x = 11